The Underlying Pathology of Autoimmune Thyroid Disease is Il-22 Independent - Hamad, Hadi H.; Raziq, Amir H. (Science Journal of University of Zakho, 2020)
The thyroid gland is frequently associated with autoimmune disease. It produces thyroid hormones responsible for controlling cellular metabolism. The current case control study  involved ninety subjects which were assigned into two equal-numbered groups of patients and apparently healthy controls. For laboratory evaluation, five millilitres of venous blood were withdrawn from individual participants, serum were collected and  stored at –20 oC to be analysed.  Immunoassay technique was used to measure the serum level of thyroid stimulating hormone (TSH), thyroxine (T4), and triiodothyronine (T3). While ELISA technique was used for measuring the serum levels of anti-thyroid peroxidase (anti-TPO) antibodies and IL-22. The results of the current study showed that, in  the patient group, thirty eight (84.44 %) subjects were diagnosed with hypothyroidism, represented by thirty five female (77.77 %) and three male (6.67 %); furthermore, seven individuals (15.56 %) were grouped as hyperthyroid patients and represented by five females  (11.11 %) and two males (4.45 %). The results also demonstrated that the serum  TSH levels  (12.04  ± 2.76) for the patients were significantly (p< 0.05) higher than that of the control group  (1.87 ± 0.15). Whereas, T3 and T4 mean serum levels ± SE were 2.05 nmol/l ±0.14; 100.66 nmol/l ± 4.76 and 2.14 nmol/l ± 0.07; 105.37 nmol/l ± 2.92 for patient and control categories, respectively. The findings of this work showed that mean serum level (IU/ml) of anti-thyroidperoxidase antibody in patient group differed significantly (P
Keywords: Autoimmune diseases; Anti-TPO; ELISA; IL-22